Association between asthma and serum adiponectin concentration in women. Issue 10 (4th April 2008) - Sood, A; Cui, X; Qualls, C; Beckett, W S; Gross, M D; Steffes, M W; Smith, L J; Jacobs, D R
Abstract : Background: The association of murine asthma with adiposity may be mediated by adiponectin, an anti-inflammatory adipokine with reduced serum concentrations in obese subjects. A study was undertaken to examine whether the serum adiponectin concentration is associated with human asthma and whether it explains the association between adiposity and asthma, particularly in women and in premenopausal women. Methods: A cross-sectional analysis was performed of 2890 eligible subjects at year 15 of the Coronary Artery Risk Development in Young Adults (CARDIA) cohort and its YALTA ancillary study who had either current asthma or never asthma at that evaluation. Obesity was defined as body mass index (BMI) ⩾30 kg/m 2 . Multivariable logistic regression analysis was performed with current asthma status as the dependent variable. Results: Women, but not men, with current asthma had a lower mean unadjusted serum adiponectin concentration than those with never asthma (p<0.001; p for sex interaction <0.001). Similarly, current asthma was related to obesity only in women (OR 3.31, 95% CI 2.00 to 5.46, p for sex interaction = 0.004); this association was little affected by adjusting for serum adiponectin. The prevalence of current asthma in premenopausal women was reduced in the highest compared with the lowest tertile of serum adiponectin concentration (OR 0.46, 95% CI 0.26 to 0.84, p = 0.03), after adjusting for BMI. However, the interaction between serum adiponectin concentration and BMI category on current asthma status was not significant in premenopausal women or women overall. Conclusions: A high serum adiponectin concentration may protect against current asthma in premenopausal women but does not explain the association between asthma and adiposity.